A low-cost close-range photogrammetric surface scanner - Koutlemanis, Panagiotis; Zabulis, Xenophon; Stivaktakis, Nikolaos; Partarakis, Nikolaos; Zidianakis, Emmanouil; Demeridou, Ioanna (Frontiers in Imaging, 2024)
A low-cost, close-range photogrammetric surface scanner is proposed, made from Computer Numerical Control (CNC) components and an off-the-shelf, consumer-grade macro camera. To achieve micrometre resolution in reconstruction, accurate and photorealistic surface digitisations, and retain low manufacturing cost, an image acquisition approach and a reconstruction method are proposed. The image acquisition approach uses the CNC to systematically move the camera and acquire images in a grid tesselation and at multiple distances from the target surface. A relatively large number of images is required to cover the scanned surface. The reconstruction method tracks keypoint features to robustify correspondence matching and uses far-range images to anchor the accumulation of errors across a large number of images utilised. Qualitative and quantitative evaluation demonstrate the efficacy and accuracy of this approach.